2020
DOI: 10.1097/ta.0000000000002713
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric trauma triage: A Pediatric Trauma Society Research Committee systematic review

Abstract: BACKGROUND Significant variability exists in the triage of injured children with most systems using mechanism of injury and/or physiologic criteria. It is not well established if existing triage criteria predict the need for intervention or impact morbidity and mortality. This study evaluated existing evidence for pediatric trauma triage. Questions defined a priori were as follows: (1) Do prehospital trauma triage criteria reduce mortality? (2) Do prehospital trauma scoring systems predict outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Pre-COVID studies have looked at the associations with likelihood of transfer from adult trauma centers to pediatric trauma centers and from lower level to higher level centers. ( 19 , 20 , 21 ) A 2020 Pediatric Trauma Society systematic review found that in general, young age, intracranial injury, and more severely injured patients are most consistently transferred. ( 21 ) Hamilton et al analyzed the National Trauma Databank from 2007-2012, and also identified female sex and lack of insurance as independent predictors of transfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-COVID studies have looked at the associations with likelihood of transfer from adult trauma centers to pediatric trauma centers and from lower level to higher level centers. ( 19 , 20 , 21 ) A 2020 Pediatric Trauma Society systematic review found that in general, young age, intracranial injury, and more severely injured patients are most consistently transferred. ( 21 ) Hamilton et al analyzed the National Trauma Databank from 2007-2012, and also identified female sex and lack of insurance as independent predictors of transfer.…”
Section: Discussionmentioning
confidence: 99%
“…( 19 , 20 , 21 ) A 2020 Pediatric Trauma Society systematic review found that in general, young age, intracranial injury, and more severely injured patients are most consistently transferred. ( 21 ) Hamilton et al analyzed the National Trauma Databank from 2007-2012, and also identified female sex and lack of insurance as independent predictors of transfer. Injuries sustained were not reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has the disadvantage of being calculated based on diagnoses during hospitalization, thus not applicable for screening at the scene. Prehospital assessment of severity in pediatric trauma cases can be challenging due to the child's anatomy and physiology ( 21 , 25 , 26 ). The sensitivity of pediatric prehospital triage tools ranging has been reported to range from 49.1% to 87.3% ( 21 ), sometimes resulting in overtriage rates higher than 20% ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, early recognition of altered mental status is essential to timely management of head trauma. [23][24][25] Early recognition of tachycardia and hypotension are core components of sepsis recognition. 26 In turn, early recognition of the critically ill or injured child leads to timely administration of evidence-based interventions linked to improved outcomes.…”
Section: Discussionmentioning
confidence: 99%